2022
DOI: 10.3390/jpm12030347
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Surgery (ERAS) in DIEP-Flap Breast Reconstructions—A Comparison of Two Reconstructive Centers with and without ERAS-Protocol

Abstract: Enhanced recovery after surgery (ERAS) is established for autologous breast reconstruction. ERAS leads to a shortened hospital stay and improved outcome after elective surgery. In this retrospective, two-center case–control study, we compared two different treatment regimens for patients undergoing a DIEP-flap breast reconstruction from two centers, one with an established ERAS protocol and one without. All patients with DIEP breast reconstructions over the period of 12 months were included. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In this study, LOS was similar at both institutions (5.5±1 days at PC and 5.5±0.9 days at CH, mean ± SD). While LOS was longer compared with other studies, it was within the range reported by another Swiss center ( 22 - 24 ). The authors hypothesize that the difference compared with centers in other countries may be due to insurance policies or preoperative counseling and expectation setting ( 25 ).…”
Section: Discussionsupporting
confidence: 75%
“…In this study, LOS was similar at both institutions (5.5±1 days at PC and 5.5±0.9 days at CH, mean ± SD). While LOS was longer compared with other studies, it was within the range reported by another Swiss center ( 22 - 24 ). The authors hypothesize that the difference compared with centers in other countries may be due to insurance policies or preoperative counseling and expectation setting ( 25 ).…”
Section: Discussionsupporting
confidence: 75%
“…Our trust follows the DIEP flap Enhanced Recovery After Surgery program to shorten inpatient stay, reduce postoperative pain, and improve outcomes. 12–14…”
Section: Methodsmentioning
confidence: 99%
“…Our trust follows the DIEP flap Enhanced Recovery After Surgery program to shorten inpatient stay, reduce postoperative pain, and improve outcomes. [12][13][14] There were 67 unipedicled and 31 bipedicled DIEP flaps (bilateral unipedicled + unilateral bipedicled). Procedure type varied slightly with some reconstructions being immediately after mastectomy (N = 63) and others delayed (N = 35).…”
Section: Patientsmentioning
confidence: 99%
“…The deep inferior epigastric perforator flap (DIEP) has become the widely accepted gold standard for breast reconstruction. Its benefits are a low donor site morbidity and due to the tissue characteristics, a superior aesthetic result of the reconstructed breast [ 4 ]. Unlike in the pioneering days of microsurgery, autologous breast reconstruction today is not only about the survival of the flap but also about the aesthetic result of the breast and the donor site.…”
Section: Introductionmentioning
confidence: 99%